2014
DOI: 10.1089/ars.2014.5836
|View full text |Cite
|
Sign up to set email alerts
|

Statins: Pleiotropic Regulators of Cardiovascular Redox State

Abstract: Lipid-lowering treatment with statins is one of the most effective therapeutic strategies in cardiovascular medicine because they reduce cardiovascular risk in both primary and secondary prevention. Despite the wellestablished links between low-density lipoprotein and cardiovascular risk, the clinical benefit from statin treatment is not fully explained by their lipid-lowering potential. A number of pleiotropic effects of statins have been described over the past decade, and their ability to suppress global ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…In fact, experimental and clinical studies have shown that statins are involved in a reduction in reperfusion injury and inflammatory reactions and in the improvement in the microcirculation. Statins are implicated in the generation of intracellular mediators, which may prevent mPTP opening and therefore preserve mitochondrial integrity and the survival of cells (Ludman et al ., ; Antoniades and Channon, ; Mihos et al ., ). However, a growing body of evidence suggests that the cardioprotective potential of statins, associated with their pleiotropic and anti‐inflammatory effects, is mediated by the up‐regulation and activation of PPARα (Balakumar and Mahadevan ; Ravingerova et al ., ).…”
Section: Effect Of Hypercholesterolaemia On Myocardial Ischaemia/repementioning
confidence: 97%
“…In fact, experimental and clinical studies have shown that statins are involved in a reduction in reperfusion injury and inflammatory reactions and in the improvement in the microcirculation. Statins are implicated in the generation of intracellular mediators, which may prevent mPTP opening and therefore preserve mitochondrial integrity and the survival of cells (Ludman et al ., ; Antoniades and Channon, ; Mihos et al ., ). However, a growing body of evidence suggests that the cardioprotective potential of statins, associated with their pleiotropic and anti‐inflammatory effects, is mediated by the up‐regulation and activation of PPARα (Balakumar and Mahadevan ; Ravingerova et al ., ).…”
Section: Effect Of Hypercholesterolaemia On Myocardial Ischaemia/repementioning
confidence: 97%
“…Statins show pleiotropic effects on endothelial function, inhibition of thrombus gene activity, the stability of atherosclerosis plaques, and decreased inflammation and OS [ 36 ]. Statins have been shown to have antioxidant effects on redox signaling of vascular and myocardial tissue by modifying NADPH oxidase activity [ 37 ]. Statins show effects on eNOS and decreased LPO [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol lowering-independent effects have been reported to contribute to the beneficial effects of statins on the cardiovascular system. These effects have been named "pleiotropic"; this term refers to all anti-inflammatory (42,43) and anti-oxidant (42,(44)(45)(46) properties attributed to the use of statins via mechanisms other than their cholesterol-lowering actions. Given the role of PVAT in regulating vascular homeostasis, it is rational to hypothesize that at least some of the beneficial effects of statins may be mediated by direct actions on PVAT.…”
Section: Targeting Pvat: the Role Of Statinsmentioning
confidence: 99%